2015
DOI: 10.1016/j.cell.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cell Generation and Turnover in the Human Heart

Abstract: The contribution of cell generation to physiological heart growth and maintenance in humans has been difficult to establish and has remained controversial. We report that the full complement of cardiomyocytes is established perinataly and remains stable over the human lifespan, whereas the numbers of both endothelial and mesenchymal cells increase substantially from birth to early adulthood. Analysis of the integration of nuclear bomb test-derived (14)C revealed a high turnover rate of endothelial cells throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
865
6
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 960 publications
(909 citation statements)
references
References 32 publications
32
865
6
6
Order By: Relevance
“…In humans, CM division rate peaks in infants and declines thereafter (Mollova et al, 2013;Bergmann et al, 2015), which is associated with rapid telomerase inhibition in low-turnover tissues and gradual telomere shortening with aging (Wright et al, 1996;Daniali et al, 2013). Interestingly, Haubner et al (2016) recently reported a case of functional recovery from severe myocardial infarction in a newborn child, at the time when telomeres are at their longest.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, CM division rate peaks in infants and declines thereafter (Mollova et al, 2013;Bergmann et al, 2015), which is associated with rapid telomerase inhibition in low-turnover tissues and gradual telomere shortening with aging (Wright et al, 1996;Daniali et al, 2013). Interestingly, Haubner et al (2016) recently reported a case of functional recovery from severe myocardial infarction in a newborn child, at the time when telomeres are at their longest.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was thought that the human heart is a post-mitotic and terminally developed organ with no cell renewal capacity, but this dogma was refuted in 2001 when enhanced myocyte cell proliferation was demonstrated following AMI [6] and then confirmed by other groups [7,8].…”
Section: Development Of the Paracrine/secretome Hypothesismentioning
confidence: 99%
“…"Regenerative medicine" or "tissue regeneration" had become to an inspired term recently since it has been realized in the last decade that many organs such as the skin display morphological plasticity and possess healing capacity instead of being a post-mitotic terminally developed organ (1,2).…”
mentioning
confidence: 99%